2004
DOI: 10.1089/1044546041649138
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Tics in Children with ADHD: Impact of Once-Daily OROS® Methylphenidate Therapy

Abstract: These data suggest that MPH-based therapy does not significantly induce or exacerbate tics in children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Blinded clinical trials of stimulant medications for ADHD in children with tics suggest that stimulants are no more commonly associated with tics as an adverse event than placebo or clonidine. [28] These data and other studies [44][45][46] suggest that during well-supervised stimulant treatment of ADHD in children with tics, the rate of tic exacerbation associated with stimulant treatment is not higher than that observed with placebo or an active drug comparator.…”
Section: Are Any Changes Required To Criterion D For Any Of the Tic Dmentioning
confidence: 74%
“…Blinded clinical trials of stimulant medications for ADHD in children with tics suggest that stimulants are no more commonly associated with tics as an adverse event than placebo or clonidine. [28] These data and other studies [44][45][46] suggest that during well-supervised stimulant treatment of ADHD in children with tics, the rate of tic exacerbation associated with stimulant treatment is not higher than that observed with placebo or an active drug comparator.…”
Section: Are Any Changes Required To Criterion D For Any Of the Tic Dmentioning
confidence: 74%
“…In a double-blind, placebo-controlled crossover study of 38 children, there was no greater risk of developing tics [101]. In another study, there was no increase in tic frequency over 2 years of treatment with OROS MPH or IR MPH versus placebo [100]. Furthermore, in a study [100] using pooled data from three placebo-controlled studies, which measured the frequency of tics in the treatment of ADHD with OROS MPH, the incidence of tics was not significantly different between treatment groups: OROS MPH 4.0%, MPH t.i.d.…”
Section: Ticsmentioning
confidence: 96%
“…Furthermore, tics naturally wax and wane, and so an increase in tics with stimulants may or may not be related to the use of the stimulant [83]. Tics that develop may be more due to the natural development of tics around ages 7 --8 [100]. About 20% of children with ADHD have chronic TDs and about 50% of those with chronic tics or Tourette syndrome (TS) have ADHD [99].…”
Section: Ticsmentioning
confidence: 99%
“…These side effects are generally associated with dose of medication and can be controlled through dosing or scheduling adjustments. There has been concern about stimulant medication inducing or exacerbating tics; however, pooled data from three placebo-controlled studies showed the incidence of tics was not significantly different across groups, therefore suggesting that stimulants do not significantly induce or exacerbate tics in children with ADHD (Palumbo, Spencer, Lynch, Co-Chien, & Faraone, 2004).…”
Section: Attention Deficit/hyperactivity Disordermentioning
confidence: 99%